Continuity in the Use of Shallow Sites of the Salado River Basin in the Pampean Region, Argentina. Issue 4 (3rd October 2016) - Frère, María Magdalena; González, María Isabel; Greco, Catriel
Abstract: This article presents 24 radiocarbon dates of different materials (animal and human bones, charcoal, and pottery) recovered from hunter-gatherer-fisher archaeological sites from the Salado River microregion, Buenos Aires Province, Argentina. We used a microregional design strategy, and considered the 14 C dates as a group to analyze them with Bayesian statistics. This was essential to the analysis of the chronology of these shallow sites, in which the soil dynamics add the archaeological materials into the A horizon sedimentary matrix. In these types of sites, the occupational events are difficult to identify, so archaeological indicators are needed to assess the temporal contexts.